Nutrition Counseling for Hypertension Patients in the Working Area of Puuwatu Health Center, Kendari City - Rosnah; Sri Yunanci V. Gobel; Petrus; Teguh Fathurrahman; Syaifudin Suhri Kasim (CV. Literasi Indonesia, 2023)
Hypertension is the factor that contributes the most to the incidence of cardiovascular disease. Hypertension needs good management so that patients do not experience complications that aggravate their hypertension. One aspect of hypertension management that patients can do independently is dietary modification which is part of lifestyle modification. The purpose of this community service is that the community who is the target group after attending counseling can increase knowledge about a balanced menu and the dangers of hypertension as an effort to prevent complications from hypertension in the Puuwatu Health Center area of Kendari City, carried out in October 2023. Methods through counseling using a pocketbook, and filling out a pre-post test questionnaire to determine the level of success of the counseling conducted. Knowledge assessment using the questionnaire method and pretest-posttest values were tested with paired test statistics. The results of the average knowledge score before counseling was 7.6 ± 1.7 and after counseling the average knowledge score was 8.4 ± 1.0. In conclusion, there is an increase in the average knowledge after being given counseling about the importance of regulating diet and diet to prevent complications of hypertension.